Changing of Chinese psychiatrists' attitudes toward consent process to treatment and its association with the China's National Mental Health Law. (January 2019) - Huang, Jingjing; Shao, Yang; Ma, Huajian; Yang, Weimin; Li, Huafang
Objective: Few studies have addressed informed consent in Chinese psychiatric practice. We wished to explore psychiatrists' attitudes toward informed consent in Shanghai after promulgation of the first national law for mental health care in China: the National Mental Health Law. Method: A total of 398 psychiatrists were recruited from seven psychiatric hospitals in Shanghai. Their anthropometric data were collected. A confidential, self-report questionnaire addressing attitudes toward the informed consent process was completed by all participants. Results: Most respondents would like to inform patients/guardians of the diagnosis (95.2%), treatment plan (93.5%), treatment goals and potential adverse effects of prescribed medications (94.7%), and alternative treatment plans (71.9%). In addition, 58.4% of psychiatrists thought that the informed consent process for physical restraint was difficult to follow. According to logistic regression, psychiatrists not trained to use the National Mental Health Law were more likely to have a negative attitude toward the informed consent process compared with those trained (adjusted odds ratio = 0.21; 95% confidence interval: 0.07–0.59; p = 0.003). Conclusions: Psychiatrists trained to use the National Mental Health Law had more positive attitudes toward the informed consent process. Lack of such training could affect the attitudes of psychiatrists toward the informed consent process in China.